2011
DOI: 10.1371/journal.pone.0022595
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligase RNF146 Regulates Tankyrase and Axin to Promote Wnt Signaling

Abstract: Canonical Wnt signaling is controlled intracellularly by the level of β-catenin protein, which is dependent on Axin scaffolding of a complex that phosphorylates β-catenin to target it for ubiquitylation and proteasomal degradation. This function of Axin is counteracted through relocalization of Axin protein to the Wnt receptor complex to allow for ligand-activated Wnt signaling. AXIN1 and AXIN2 protein levels are regulated by tankyrase-mediated poly(ADP-ribosyl)ation (PARsylation), which destabilizes Axin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
212
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(228 citation statements)
references
References 36 publications
6
212
0
Order By: Relevance
“…Recent studies have demonstrated that ARTD5-and 6-(formerly Tankyrase1 and 2) dependent PARylation of axin results in the recruitment of the ubiquitin E3 ligase RNF146 and subsequent pUb-dependent proteasomal degradation of axin, a negative regulator of WNT signalling 9,10,25 . Similarly, 3BP2 is substrate of ARTD5 and RNF146.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that ARTD5-and 6-(formerly Tankyrase1 and 2) dependent PARylation of axin results in the recruitment of the ubiquitin E3 ligase RNF146 and subsequent pUb-dependent proteasomal degradation of axin, a negative regulator of WNT signalling 9,10,25 . Similarly, 3BP2 is substrate of ARTD5 and RNF146.…”
Section: Discussionmentioning
confidence: 99%
“…PARylation regulates various cellular processes, such as DNA repair, specific signalling processes and gene transcription 5 . The functional consequences of PARylation are mediated by distinct protein domains, including macrodomains, WWE (named after two conserved tryptophan residues and a glutamate residue) and PAR-binding zinc-finger (PBZ) domains [6][7][8][9][10] . In contrast to the function of class 1 ARTD enzyme-mediated PARylation, little is known about the biological relevance of mono-ADP-ribosyltransferases.…”
mentioning
confidence: 99%
“…FuGENE 6 HD (Roche Applied Science) was used for plasmid transfection in RPE cells. Epitope-tagged Trabid, HectD1, APC, Tankyrase (TNKS1) and RNF146 constructs have been described (17,24,25). Recombinant mouse Wnt3a was purchased from R & D Systems.…”
Section: Methodsmentioning
confidence: 99%
“…This protein was incubated with lysates from HEK293 cells expressing HA-HectD1. To control for binding specificity, we used a Glu-Glu-tagged APC3 protein (gg-APC3) purified from insect cells (27) and lysates from HEK293 cells expressing HATankyrase (TNKS1), a poly(ADP-ribosyl)ase that binds the E3 ligase RNF146 to cooperatively down-regulate Axin (17). Following pulldown with anti-Glu-Glu-agarose, we detected an interaction between HA-HectD1 and the APC ARD, but only weak association between HA-HectD1 and APC3 (Fig.…”
Section: Identification Of E3 Ubiquitin Ligase Hectd1 In a Trabidmentioning
confidence: 99%
See 1 more Smart Citation